Language of promotion in Malaysian banking brochures - Ummul K. Ahmad,; Chai, Hong Chong (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Promotional language or language used to promote a product or service is commonly used in advertisements, job applications and sales promotional letters. Brochures which aim at selling products and services also typically employ the same mode. Studies focusing on promotional brochures such as tourist brochures and university brochures have shown that brochures employ varied rhetorical structures while sharing similar communicative purposes. Financial institutions such as banks also produce brochures to advertise their products and services to the public. This paper presents results from a corpus-based study of 50 Malaysian banking brochures collected from ten Malaysian banks. Informational structure analysis of the corpus have suggested that banking brochures typically have five strategic moves which include announcing the products, attracting attention, establishing credentials, introducing products and calling for action—moves indicating that they are indeed promotional in nature. However, findings from our corpus differ somewhat from other studies focusing on similar genres in that banking brochures do not have explicit moves for targeting the market, motivating the audience and locating the services as found in tourist brochures. They do, however, integrate strategic visual images for compensating the absent moves. The study shows the multidimensional aspects of promotional language and the use of interdiscursive resources in the genre of brochure.